2002
DOI: 10.1051/gse:2001006
|View full text |Cite
|
Sign up to set email alerts
|

Association of a missense mutation in the bovine leptin gene with carcass fat content and leptin mRNA levels

Abstract: -Previously, we have shown that alleles of the BM1500 microsatellite, located 3.6 kb downstream of the leptin gene in cattle, were associated with carcass fat measures in a population of 154 unrelated beef bulls. Subsequently, a cytosine (C) to thymine (T) transition that encoded an amino acid change of an arginine to a cysteine was identified in exon 2 of the leptin gene. A PCR-RFLP was designed and allele frequencies in four beef breeds were correlated with levels of carcass fat. The T allele was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
3
23

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(169 citation statements)
references
References 28 publications
(36 reference statements)
7
136
3
23
Order By: Relevance
“…Polymorphisms have been reported in the coding regions of the LEP gene that show considerable associations with feed intake [30,29,39], carcass merit [4,37,25], serum leptin concentration [31] and milk quantity and quality [5,32,34,8] in cattle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymorphisms have been reported in the coding regions of the LEP gene that show considerable associations with feed intake [30,29,39], carcass merit [4,37,25], serum leptin concentration [31] and milk quantity and quality [5,32,34,8] in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Leptin has been considered as a candidate gene for performance, carcass and meat quality traits in beef cattle [17,4,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When fat mass enlarges leptin is synthesized and secreted by the white fat cells, thus providing information to the hypothalamus about the excessive amount of fat deposits (Schwarz et al, 1996). Buchanan et al (2002) found, that higher leptin mRNA expression was in the cattle homozygous for the thymine (T) allele. This substitution having major biological effect.…”
Section: Article Infomentioning
confidence: 99%
“…The main role of leptin could be to help animals to adapt to period of undernutrition. Indeed, the rapid decrease in leptinemia in underfeed animals could be an acute signal to stimulate refeeding behavior and glucocorticoid secretion, to decrease thyroid activity, energy expenditure, insulin sensitivity and protein synthesis and to block reproduction (Chilliard et al, 2005). The leptin gene is located on bovine chromosome 4 (BTA4) (Buchanan et al, 2002) and consists of 3 exon, with exon 2 and 3 containing the protein coding region (Tian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%